A decision support tool for assessing entanglement risk to protected species from fixed-gear fisheries with applications to North Atlantic right whales (Eubalaena glacialis) in the Northwest Atlantic - Burton Shank; Alicia S. Miller; Laura Solinger; Michael J. Asaro; Douglas Sigourney; Alessandra Huamani; Marisa L. Trego; Crystal Franco; Jason J. Roberts; Jeffrey D. Walker; André L. Price; Mareike D. Duffing Romero; et al. (Frontiers in Marine Science, 2025)
Entanglement is one of the primary anthropogenic threats to the North Atlantic right whale ( Eubalaena glacialis ; right whale) whose habitat overlaps fixed-gear fishing grounds in the Northwest Atlantic with entanglements representing around half of the mortality and serious injury incidents. Right whale mortality has reached levels that require intervention under the Marine Mammal Protection Act, creating the need for a tool that can compare the relative benefits of risk reduction management measures under consideration. To address this need, National Marine Fisheries Service developed a Decision Support Tool (DST) which has undergone continued development since 2019 and is introduced here as the Woods Hole Analysis of Line Entanglement (WHALE) DST. This tool calculates relative risk as the product of (1) the density of endlines associated with fixed-gear fishing at a given location and month, (2) the entanglement severity that endlines pose based on the specific configuration of the gear, and (3) the estimated density of right whales at the given location and month. The model is novel in its capacity to quantify reductions in entanglement risk by simultaneously assessing a variety of overlapping management actions such as time/area closures, weakening of rope, and other adaptations of gear configurations that reduce endlines or make them less dangerous. We demonstrate the functionality of the WHALE DST by applying management actions implemented in 2021. While originally developed for right whale conservation, the WHALE DST is adaptable for evaluating spatiotemporal entanglement risk reduction for other protected species management and marine spatial planning activities.

A Tale of Two Shrimps—Speciation and Demography of Two Sympatric Shrimp Species From Hydrothermal Vents - Pierre Methou; Shannon B. Johnson; John Sherrin; Timothy M. Shank; Chong Chen; Verena Tunnicliffe (Molecular Ecology, 2025)
Hydrothermal vents can serve as natural laboratories to study speciation processes due to their fragmented distribution, often with geographic barriers between habitats. Two sympatric species of Rimicaris shrimps occur at vents on the Izu‐Bonin‐Mariana volcanic arc: Rimicaris loihi also occurs near Hawai’i and R. cambonae is present on the Tonga Arc. These two species biogeographically co‐occur and are genetically similar, raising questions about their speciation mechanisms, how they maintain distinct species, and whether interbreeding occurs. Here, we used barcoding and shotgun sequencing to test their genetic isolation and investigate their speciation process. We also evaluated population demography over 10 years to assess population densities and sex ratios at vents. Our results supported R. cambonae and R. loihi as two distinct species despite sympatry throughout part of their range. We also observed regional‐scale genetic structure among R. loihi populations from the Izu‐Bonin‐Mariana volcanic arc, despite high dispersal potential. Finally, we found concomitant variations of shrimp densities and genetic diversity following fluctuations in geological and venting activities over a decade. A combination of geological instability, ocean currents dynamics and sea‐level changes might drive temporary isolation among these local populations. We suggest that similar factors, with longer isolation periods, may also have promoted speciation between the two Rimicaris species, whereas distinct life‐history traits could strengthen and maintain reproductive barriers. Overall, we found that the two species with large geographic distributions had significant patterns of genetic partitioning on a volcanic arc; this scenario contrasts with those observed previously at vents from mid‐ocean ridges or back‐arc basin systems.

Microplastic accumulation visually and fluorescently undetectable within deepwater corals of the remote equatorial Pacific - Maxwell S. Helmberger; Steven Auscavitch; Justin Linehan; Timothy M. Shank; Erik Cordes; Randi D. Rotjan (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Quantifying the relative importance of biotic and abiotic factors in landscape-based models of stream fish distributions - Christopher A. Custer; Douglas P. Fischer; Geoffrey Smith; Aaron Henning; Megan Kepler Schall; Matthew K. Shank; Timothy A. Wertz; Tyler Wagner (Community Ecology, 2024)
Lotic fish species distributions are frequently predicted using remotely sensed habitat variables that characterize the adjacent landscape and serve as proxies for instream habitat. Recent advancements in statistical methodology, however, allow for leveraging fish assemblage data when predicting distributions. This is important because assemblage composition likely provides better information about instream habitat compared to landscape-derived metrics and therefore may improve predictions. To better understand the value of using multi-species fish data in species distribution modeling, we fit two conditional random fields (CRF) models to quantify the relative importance of fish assemblage co-occurrence, landscape-derived habitat variables, and interactions between these two predictor groups (i.e., effects of co-occurrence could be context-dependent) at over 1200 stream catchments in Pennsylvania, USA. We first compared predictive performance of CRF models against traditionally used single-species logistic regressions (generalized linear models; GLMs) and found that inclusion of fish assemblage data often improved predictive performance. The multi-species CRF models performed significantly better at predicting occurrence for 63% of species with an average percent increase in AUC of 25% compared to GLMs. Furthermore, the CRF identified species co-occurrences as more informative, and thus relatively more important, at predicting occurrence than the other effect types. The CRF also suggested that allowing these biotic effects to be context-dependent was important for predicting occurrence of many species. These findings illustrate the value of fish assemblage data for landscape-scale species distribution modeling and leveraging this information can improve predictions and inferences to help inform the management and conservation of freshwater fishes.

Implications of transient methane flux on associated biological communities in high-arctic seep habitats, Storbanken, Norwegian Barents Sea - Taylor P. Heyl; Giuliana Panieri; Daniel J. Fornari; Rune Mattingsdal; Simone Sauer; Haoyi Yao; Luke McCartin; Elisabeth McElwee; Timothy M. Shank (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

New Opportunities and Untapped Scientific Potential in the Abyssal Ocean - Jeffrey J. Marlow; Rika E. Anderson; Anna-Louise Reysenbach; Jeffrey S. Seewald; Timothy M. Shank; Andreas P. Teske; V. Dorsey Wanless; S. Adam Soule (Frontiers in Marine Science, 2022)
The abyssal ocean covers more than half of the Earth’s surface, yet remains understudied and underappreciated. In this Perspectives article, we mark the occasion of the Deep Submergence Vehicle Alvin’s increased depth range (from 4500 to 6500 m) to highlight the scientific potential of the abyssal seafloor. From a geologic perspective, ultra-slow spreading mid-ocean ridges, Petit Spot volcanism, transform faults, and subduction zones put the full life cycle of oceanic crust on display in the abyss, revealing constructive and destructive forces over wide ranges in time and space. Geochemically, the abyssal pressure regime influences the solubility of constituents such as silica and carbonate, and extremely high-temperature fluid-rock reactions in the shallow subsurface lead to distinctive and potentially unique geochemical profiles. Microbial residents range from low-abundance, low-energy communities on the abyssal plains to fast growing thermophiles at hydrothermal vents. Given its spatial extent and position as an intermediate zone between coastal and deep hadal settings, the abyss represents a lynchpin in global-scale processes such as nutrient and energy flux, population structure, and biogeographic diversity. Taken together, the abyssal ocean contributes critical ecosystem services while facing acute and diffuse anthropogenic threats from deep-sea mining, pollution, and climate change.

Corrigendum: Marine Genetic Resources in Areas Beyond National Jurisdiction: Promoting Marine Scientific Research and Enabling Equitable Benefit Sharing - Alex D. Rogers; Amy Baco; Elva Escobar-Briones; Duncan Currie; Kristina Gjerde; Judith Gobin; Marcel Jaspars; Lisa Levin; Katrin Linse; Muriel Rabone; Eva Ramirez-Llodra; Javier Sellanes; et al. (Frontiers in Marine Science, 2021)

Marine Genetic Resources in Areas Beyond National Jurisdiction: Promoting Marine Scientific Research and Enabling Equitable Benefit Sharing - Alex D. Rogers; Amy Baco; Elva Escobar-Briones; Duncan Currie; Kristina Gjerde; Judith Gobin; Marcel Jaspars; Lisa Levin; Katrin Linse; Muriel Rabone; Eva Ramirez-Llodra; Javier Sellanes; et al. (Frontiers in Marine Science, 2021)
Growing human activity in areas beyond national jurisdiction (ABNJ) is driving increasing impacts on the biodiversity of this vast area of the ocean. As a result, the United Nations General Assembly committed to convening a series of intergovernmental conferences (IGCs) to develop an international legally-binding instrument (ILBI) for the conservation and sustainable use of marine biological diversity of ABNJ [the biodiversity beyond national jurisdiction (BBNJ) agreement] under the United Nations Convention on the Law of the Sea. The BBNJ agreement includes consideration of marine genetic resources (MGR) in ABNJ, including how to share benefits and promote marine scientific research whilst building capacity of developing states in science and technology. Three IGCs have been completed to date with the fourth delayed by the Covid pandemic. This delay has allowed a series of informal dialogues to take place between state parties, which have highlighted a number of areas related to MGR and benefit sharing that require technical guidance from ocean experts. These include: guiding principles on the access and use of MGR from ABNJ; the sharing of knowledge arising from research on MGR in ABNJ; and capacity building and technology transfer for developing states. In this paper, we explain what MGR are, the methods required to collect, study and archive them, including data arising from scientific investigation. We also explore the practical requirements of access by developing countries to scientific cruises, including the sharing of data, as well as participation in research and development on shore whilst promoting rather than hindering marine scientific research. We outline existing infrastructure and shared resources that facilitate access, research, development, and benefit sharing of MGR from ABNJ; and discuss existing gaps. We examine international capacity development and technology transfer schemes that might facilitate or complement non-monetary benefit sharing activities. We end the paper by highlighting what the ILBI can achieve in terms of access, utilization, and benefit sharing of MGR and how we might future-proof the BBNJ Agreement with respect to developments in science and technology.

Deep-Sea Debris in the Central and Western Pacific Ocean - Diva J. Amon; Brian R. C. Kennedy; Kasey Cantwell; Kelley Suhre; Deborah Glickson; Timothy M. Shank; Randi D. Rotjan (Frontiers in Marine Science, 2020)

Oceanographic Drivers of Deep-Sea Coral Species Distribution and Community Assembly on Seamounts, Islands, Atolls, and Reefs Within the Phoenix Islands Protected Area - Steven R. Auscavitch; Mary C. Deere; Abigail G. Keller; Randi D. Rotjan; Timothy M. Shank; Erik E. Cordes (Frontiers in Marine Science, 2020)

Animal Community Dynamics at Senescent and Active Vents at the 9°N East Pacific Rise After a Volcanic Eruption - Sabine Gollner; Breea Govenar; Pedro Martinez Arbizu; Lauren S. Mullineaux; Susan Mills; Nadine Le Bris; Markus Weinbauer; Timothy M. Shank; Monika Bright (Frontiers in Marine Science, 2020)

Multiple spatially distinct introductions and not range expansion may explain colonization history in a non-native marine shrimp - Eleanor K. Bors; James T. Carlton; Timothy M. Shank (Marine Biology, 2019)

Evolutionary and biogeographical patterns of barnacles from deep‐sea hydrothermal vents - Santiago Herrera; Hiromi Watanabe; Timothy M. Shank (Molecular Ecology, 2015)
The characterization of evolutionary and biogeographical patterns is of fundamental importance to identify factors driving biodiversity. Due to their widespread but discontinuous distribution, deep‐sea hydrothermal vent barnacles represent an excellent model for testing biogeographical hypotheses regarding the origin, dispersal and diversity of modern vent fauna. Here, we characterize the global genetic diversity of vent barnacles to infer their time of radiation, place of origin, mode of dispersal and diversification. Our approach was to target a suite of multiple loci in samples representing seven of the eight described genera. We also performed restriction‐site associated DNA sequencing on individuals from each species. Phylogenetic inferences and topology hypothesis tests indicate that vent barnacles have colonized deep‐sea hydrothermal vents at least twice in history. Consistent with preliminary estimates, we find a likely radiation of barnacles in vent ecosystems during the Cenozoic. Our analyses suggest that the western Pacific was the place of origin of the major vent barnacle lineage, followed by circumglobal colonization eastwards through the Southern Hemisphere during the Neogene. The inferred time of radiation rejects the classic hypotheses of antiquity of vent taxa. The timing and the mode of origin, radiation and dispersal are consistent with recent inferences made for other deep‐sea taxa, including nonvent species, and are correlated with the occurrence of major geological events and mass extinctions. Thus, we suggest that the geological processes and dispersal mechanisms discussed here can explain the current distribution patterns of many other marine taxa and have played an important role shaping deep‐sea faunal diversity. These results also constitute the critical baseline data with which to assess potential effects of anthropogenic disturbances on deep‐sea ecosystems.

Chemistry, Temperature, and Faunal Distributions at Diffuse-Flow Hydrothermal Vents: Comparison of Two Geologically Distinct Ridge Systems - George Luther; Amy Gartman; Mustafa Yücel; Andrew Madison; Tommy Moore; Heather Nees; Donald Nuzzio; Arunima Sen; Richard Lutz; Timothy Shank; Charles Fisher (Oceanography, 2012)

The East Pacific Rise Between 9°N and 10°N: Twenty-Five Years of Integrated, Multidisciplinary Oceanic Spreading Center Studies - Daniel Fornari; Karen Von Damm; Julia Bryce; James Cowen; Vicki Ferrini; Allison Fundis; Marvin Lilley; George Luther; Lauren Mullineaux; Michael Perfit; M. Florencia Meana-Prado; Kenneth Rubin; et al. (Oceanography, 2012)

Incongruent patterns of genetic connectivity among four ophiuroid species with differing coral host specificity on North Atlantic seamounts - Walter Cho; Timothy M. Shank (Marine Ecology, 2010)
Seamounts are considered to play a defining role in the evolution and diversity of marine fauna, acting as ‘stepping‐stones’ for dispersal, regional centers of genetic isolation and speciation, and refugia for deep‐sea populations. This study focused on the patterns of dispersal and genetic connectivity of four seamount ophiuroid species ( Asteroschema clavigera , Ophiocreas oedipus , Ophioplinthaca abyssalis , and Ophioplinthaca chelys ) displaying differing levels of associative (epifaunal) specificity to cold‐water coral hosts inhabiting the New England and Corner Rise Seamount chains, and Muir Seamount in the Northwestern Atlantic. Analyses of mt16S and mtCOI revealed evidence for recent population expansion and high gene flow for all four species. However, species‐specific genetic differentiation was significant based on seamount region and depth. Significant differences were found among regional seamount groups for A. clavigera , within seamount regions and seamounts for O. chelys , among 250‐m depth intervals for A. clavigera , among 100‐m depth intervals for O. oedipus , and there were indications of isolation by distance for A. clavigera and O. oedipus . In addition, A. clavigera and O. oedipus , broadcast spawners with high fidelity to specific coral hosts, displayed predominantly westward historical migration, whereas the ophioplinthacids, with lower host‐specificity, displayed predominantly eastward migration. No congruent patterns of historical migration were evident among species and seamounts, yet these patterns can be correlated with species‐specific host specificity, specific depth strata, and dispersal strategies. Conservation efforts to protect seamount ecosystems should promote multi‐species approaches to genetic connectivity, and consider the impact of the ‘dependence’ of biodiversity on host fauna in these vulnerable marine ecosystems.

The composition and density of fauna utilizing burrow microhabitats created by a non-native burrowing crustacean (Sphaeroma quoianum) - Timothy M. Davidson; Alan L. Shanks; Steven S. Rumrill (Biological Invasions, 2010)

Seamount Sciences: Quo Vadis? - Hubert Staudigel; Anthony Koppers; J. William Lavelle; Tony Pitcher; Timothy Shank (Oceanography, 2010)

From the Guest Editors - Hubert Staudigel; Anthony Koppers; J. William Lavelle; Tony Pitcher; Timothy Shank (Oceanography, 2010)

BOOK REVIEW | The Silent Deep: The Discovery, Ecology, and Conservation of the Deep Sea - Timothy Shank (Oceanography, 2010)

Defining the Word "Seamount" - Hubert Staudigel; Anthony Koppers; J. William Lavelle; Tony Pitcher; Timothy Shank (Oceanography, 2010)

Spotlight: New England and Corner Rise Seamounts - Timothy Shank (Oceanography, 2010)

Seamounts: Deep-Ocean Laboratories of Faunal Connectivity, Evolution, and Endemism - Timothy Shank (Oceanography, 2010)

Mid-Ocean Ridge Exploration with an Autonomous Underwater Vehicle - Dana Yoerger; Albert Bradley; Michael Jakuba; Maurice Tivey; Christopher German; Timothy Shank; Robert Embley (Oceanography, 2007)

Autonomous and Remotely Operated Vehicle Technology for Hydrothermal Vent Discovery, Exploration, and Sampling - Dana Yoerger; Albert Bradley; Michael Jakuba; Christopher German; Timothy Shank; Maurice Tivey (Oceanography, 2007)

Biodiversity and Biogeography of Hydrothermal Vent Species: Thirty Years of Discovery and Investigations - Eva Ramirez-Llodra; Timothy Shank; Christopher German (Oceanography, 2007)

Toward a mechanistic understanding of larval dispersal: insights from genomic fingerprinting of the deep‐sea hydrothermal vent tubeworm Riftia pachyptila - Timothy M. Shank; Kenneth M. Halanych (Marine Ecology, 2007)
Larval dispersal is critical for the maintenance of species populations in patchy and ephemeral hydrothermal vent habitats. On fast‐spreading ridges, such as the East Pacific Rise, rates of habitat turnover are comparable to estimated lifespans of many of the inhabiting species. Traditionally, dispersal questions have been addressed with two very different approaches, larval studies and population genetics. Population genetic studies of vent‐endemic species have been informative for determining whether patterns of dispersal are suggestive of stepping stone or island models and estimating rates of gene flow (effective migrants per generation) over broad geographic ranges. However, these studies leave fundamental questions unanswered about the specific mechanisms by which larvae disperse and species maintain their populations and biogeographic ranges. With the goal of examining genetic structure and elucidating alternative larval dispersal mechanisms, we employed a genomic DNA fingerprinting technique, amplified fragment length polymorphisms (AFLPs). To assess the potential utility of AFLPs, and genetic structure of the hydrothermal vent tubeworm Riftia pachyptila , genomic ‘fingerprints’ were recovered from 29 individuals from five vent fields spanning a distance of up to c. 5000 km along the East Pacific Rise. In contrast to previous population genetic studies that found little to no genetic structure using allozymes and mitochondrial DNA, genetic analyses of 630 polymorphic AFLP loci identified distinct subclades within R. pachyptila populations. Significant levels of differentiation were observed among populations from all vent regions as well as within each region. Discrete assemblages of tubeworms separated by as little as c. 400 m within a given vent region were genetically distinguishable and cohorts (based on size‐frequency distribution) within an aggregation were found to be most closely related. These results suggest that mechanisms of larval dispersal act to retain cohort fidelity in R. pachyptila .

Off‐axis symbiosis found: characterization and biogeography of bacterial symbionts of Bathymodiolus mussels from Lost City hydrothermal vents - Eric G. DeChaine; Amanda E. Bates; Timothy M. Shank; Colleen M. Cavanaugh (Environmental Microbiology, 2006)
Summary Organisms at hydrothermal vents inhabit discontinuous chemical ‘islands’ along mid‐ocean ridges, a scenario that may promote genetic divergence among populations. The 2003 discovery of mussels at the Lost City Hydrothermal Field provided a means of evaluating factors that govern the biogeography of symbiotic bacteria in the deep sea. The unusual chemical composition of vent fluids, the remote location, and paucity of characteristic vent macrofauna at the site, raised the question of whether microbial symbioses existed at the extraordinary Lost City. If so, how did symbiotic bacteria therein relate to those hosted by invertebrates at the closest known hydrothermal vents along the Mid‐Atlantic Ridge (MAR)? To answer these questions, we performed microscopic and molecular analyses on the bacteria found within the gill tissue of Bathymodiolus mussels (Mytilidae, Bathymodiolinae) that were discovered at the Lost City. Here we show that Lost City mussels harbour chemoautotrophic and methanotrophic endosymbionts simultaneously. Furthermore, populations of the chemoautotrophic symbionts from the Lost City and two sites along the MAR are genetically distinct from each other, which suggests spatial isolation of bacteria in the deep sea. These findings provide new insights into the processes that drive diversification of bacteria and evolution of symbioses at hydrothermal vents.